Divergent Total Syntheses of Six Ganoderma Meroterpenoids: A Bioinspired Two-Phase Strategy - Zhang, Fen; Zhao, Yu-Ming (Synlett, 2020)
We briefly highlight our recent work on the total synthesis of six Ganoderma phenolic meroterpenoids: ganocins A–C, ganocochlearins A–D, and cochlearol T. Critical to this success was a bioinspired two-phase strategy that featured an early-stage rapid construction of a common planar tricyclic intermediate and late-stage highly selective transformations of this intermediate into various Ganoderma meroterpenoids. Key steps of the synthesis include a biomimetic ortho-quinone methide intramolecular hetero-Diels–Alder reaction, a Stahl-type oxidative aromatization, a nucleophilic dearomatization of a phenol, a regioselective 1,4-reduction of a dienone, a site-selective Mukaiyama hydration, and an intramolecular oxa-Michael addition/triflation cascade.
Keywords: divergent synthesis; meroterpenoids; biomimetic synthesis; total synthesis